Anesthetic complications in patients with chronic anemia (Colombia Medica, 1986)
Out of 74 patients with chronic anemia undergoing diverse types of elective surgery, 25% suffered important cardiovascular disturbances, probably due to surgical and anesthetic techniques interfering with compensatory mechanisms for the anemia, and that may facilitate a cardiovascular collapse.Therefore, it is proposed that 10 g% of Hb should be kept at the minimum acceptable level for elective surgery to maintain adequate tissue oxygenation to the most important organs when a stressful situation is present, like the surgery itself. Lower values of Hb indicate postponement of the surgical procedure and an appropriate therapy. Transfusion, if given, should be shown, and red cell concentrates are to be preferred.